2013
DOI: 10.1155/2013/985285
|View full text |Cite
|
Sign up to set email alerts
|

Increased Haematopoietic Supportive Function of USSC from Umbilical Cord Blood Compared to CB MSC and Possible Role of DLK-1

Abstract: Multipotent stromal cells can be isolated from a variety of different tissues in the body. In contrast to stromal cells from the adult bone marrow (BM) or adipose tissue, cord blood (CB) multipotent stromal cells (MSC) are biologically younger. Since first being described by our group, delta like 1 homologue (DLK-1) was determined as a discriminating factor between the distinct cord blood-derived subpopulations: the unrestricted somatic stromal cells (USSC), which lack adipogenic differentiation capacity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Neonatal USSCs can be easily differentiated into the osteogenic and chondrogenic lineage in vitro but can only be differentiated into the adipogenic lineage after coculture with CB MSCs [33]. Detailed characterization of the individual inherent differentiation capacity is available [30, 3436]. Therefore, neonatal stromal cells (like USSCs) can be assumed to provide favorable features for developmental toxicity testing to assess the potential toxicity of drug candidates and chemicals in the neonatal system [37].…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal USSCs can be easily differentiated into the osteogenic and chondrogenic lineage in vitro but can only be differentiated into the adipogenic lineage after coculture with CB MSCs [33]. Detailed characterization of the individual inherent differentiation capacity is available [30, 3436]. Therefore, neonatal stromal cells (like USSCs) can be assumed to provide favorable features for developmental toxicity testing to assess the potential toxicity of drug candidates and chemicals in the neonatal system [37].…”
Section: Introductionmentioning
confidence: 99%
“… 29-33 Kogler et al and our group characterized human cord blood (hCB)-derived unrestricted somatic stem cells (USSCs) and studied their proliferation, expansion, gene and cytokine expression, epigenetic modification, and lineage differentiation in various models. 34-37 We were the first to demonstrate that USSCs migrate to the site of injury, suppress inflammation, reduce hydrocephalus, improve myelination as well as neurodevelopmental outcomes in a premature rabbit pup model of IVH. 38 , 39 Other investigators show that USSCs induce significant axonal regrowth and effectively improve long-term functional locomotory and neurobehavioral recovery.…”
Section: Introductionmentioning
confidence: 98%
“…Former results indicated a correlation of the absent adipogenic potential and the expression of DLK1 (delta, Drosophila homolog-like 1) in USSC, since USSC but not CBSC express DLK1 [5]. Recent results suggested that DLK1 might not be the sole factor responsible for the inhibition of in vitro adipogenesis in USSC [6]. In microarray and PCR analyses, the expression of HOX (homeobox) genes was defined as additional distinguishing feature: USSC completely lack HOX gene expression, while CBSC are HOX positive [7].…”
Section: Introductionmentioning
confidence: 99%
“…In microarray and PCR analyses, the expression of HOX (homeobox) genes was defined as additional distinguishing feature: USSC completely lack HOX gene expression, while CBSC are HOX positive [7]. Furthermore, USSC can be discriminated from CBSC on the basis of their higher hematopoiesis-supporting capacity in coculture experiments [6]. …”
Section: Introductionmentioning
confidence: 99%